Flexible and coatable insulating silica aerogel/polyurethane composites via soft segment control. (8th February 2019) - Cho, Jaehyun; Jang, Han Gyeol; Kim, Seong Yun; Yang, Beomjoo
Abstract: We herein propose a facile approach to fabricate foldable and coatable silica aerogel polyurethane composites (APCs). For the flexibility control, the soft segment of polyurethane (PU) is manipulated. The change in soft segment length induces a difference in overall glass transition temperature of PU. When the silica aerogel content is increased, the PU with a shorter soft segment length shows brittle fracture behavior, while the PU with a longer soft segment length shows no breakage after bending. The thermal insulation properties of APCs were enhanced by 72% reduction in thermal conductivity upon 30 wt% aerogel loading and theoretically verified by a micromechanics-based thermal conductivity model considering the effects of interface and agglomeration. In addition, for the combustion behavior measurements, heat release rate and heat release capacity are substantially reduced for the APCs compared to neat PUs. Those enhanced thermal insulation properties may have a commercial impact on thermal insulation applications.